Estudos de separação de lignina do licor negro kraft em diferentes condições experimentais: caracterização e fracionamento - Oliveira, Caroline Tirolla (2016)
The processes of separation and isolation of Kraft lignin obtained have been insufficiently resear ched, since much of the lignin of liqueurs obtained industrially is burned for energy recovery and carbon sources in the industrial processes. Currently, with the technological innovation targeting the pulp and paper industries, it is increasingly importan t to obtain lignin in simple and economically viable way. In addition, it is very important to find conditions under which the proceedings begin minimum degradation into lignin structures. In this work, the concentrated liquor lignin from Kraft pulp proces s was precipitated in acid medium in different conditions of pH and variable times of exposure to acid conditions of precipitation. It was done later, ash analysis, calorific power, Scanning Electron Microscopy with X - ray Spectroscopy (SEM/EDS); Fourier Tr ansform Infrared Spectroscopy (FTIR) and Ultraviolet - Visible Spectrophotometry precipitated (UV - VIS) for the characterization of the lignins and the filtered, for the characterization of the soluble fractions. A general analysis of the results showed that the best yield has occurred in 15 minutes of precipitation time for the pH of 6.71 (less acidic) among all employees. In the second test, the precipitations were performed at pH 2, 4 and 6 and with a time of 5 and 15 minutes, in which was got better yields and lower salt content in lignin. It has been applied statistical analysis in all the results, which many of them were considered equal. Thus, the best case was considered carried out at pH 6 at the time of 5 minutes , since it uses less hydrochloric acid are to perform precipitation. In parallel, it has been done tests to assess the possibility of separate fragments of lignin and sugars. The preliminary tests were conducted with phenol, simulating the lignin, and glucose, simulating the sugars. In order t o carry out this separation was used cellulose acetate Hydrogel as stationary phase in a preparative scale. In the first test conducted in a time of 30 minutes, it was possible to observe that there was a clear separation of phenol and glucose. In the seco nd test, in which the parameters were refined, like the elution time (55 minutes), it was possible to note a great improvement in the separation. The test of fractionation was carried out in order to simulate future tests to improve the conditions of ferme ntation of residual sugar produced by hydrolysis of cellulose waste involved in the production of second - generation ethanol.